2005
DOI: 10.1007/s00330-005-2862-2
|View full text |Cite
|
Sign up to set email alerts
|

Dark-lumen magnetic resonance colonography in patients with suspected sigmoid diverticulitis: a feasibility study

Abstract: To assess dark-lumen magnetic resonance colonography (MRC) for the evaluation of patients with suspected sigmoid diverticulitis. Forty patients with suspected sigmoid diverticulitis underwent MRC within 72 h prior to conventional colonoscopy (CC). A three-dimensional T1-weighted volumetric interpolated breath-hold examination sequence was acquired after an aqueous enema and intravenous administration of gadolinium-based contrast agents. All MRC data were evaluated by two radiologists. Based on wall thickness a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
6

Year Published

2007
2007
2022
2022

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(38 citation statements)
references
References 39 publications
1
31
0
6
Order By: Relevance
“…The use of magnetic resonance colonography for the diagnosis of ACD was investigated by Ajaj et al [43]. This feasibility study reported a promising sensitivity of 86% and specificity of 92%.…”
Section: Discussionmentioning
confidence: 98%
“…The use of magnetic resonance colonography for the diagnosis of ACD was investigated by Ajaj et al [43]. This feasibility study reported a promising sensitivity of 86% and specificity of 92%.…”
Section: Discussionmentioning
confidence: 98%
“…MRI has the advantage that no ionizing radiation and intravenous contrast medium are needed to reach a higher soft tissue contrast than CT. MRI is increasingly used in the acute setting for patients with acute abdominal pain, but accuracy data are still limited. Based on studies with small numbers of patients, sensitivity and specificity of MRI for diagnosing ACD vary between 86 and 100% and 88 and 100% (level B [67,68] and level C [69,70]).…”
Section: Clinical Diagnosis and Radiological Imagingmentioning
confidence: 99%
“…Initial results suggest MRC to be sensitive and specific for the detection of clinically relevant colorectal polyps and carcinomas (12)(13)(14). Furthermore, moderate and severe bowel wall inflammation can be accurately depicted (15)(16)(17). Regarding side-effects of MRC, no complications have been reported so far.…”
Section: Discussionmentioning
confidence: 99%